Recurrent spinal cord compression due to extramedullary hematopoiesis in thalassemia patient: Case report. Issue 25 (24th June 2022) - Abbarh, Shahem; Al-Mashdali, Abdulrahman F.; Abdelrazek, Mohamed; Gurusamy, Venkada Manickam; Yassin, Mohamed A.
Abstract: Introduction: Spinal cord compression secondary to extramedullary hematopoiesis (EMH) is a rare condition. Variable treatment options have been reported with different efficacy and recurrence rate. Due to its rarity, no clear optimal management guidelines have been established yet. Patient concerns and diagnosis: We report a recurrence of spinal cord compression secondary to EMH in a 19-year-old male, with a background of transfusion-dependent beta-thalassemia on luspatercept, who presented with weakness in both lower limbs. Interventions and outcomes: He was treated successfully both times with radiotherapy. Conclusion: Early diagnosis and management of EMH compressing the spinal cord are essential to prevent permanent neurological damage. Diagnosis should be suspected based on the clinical presentation and magnetic resonance imaging findings in a patient with a history of ineffective hemopoiesis. Treatment option remains controversial. Radiotherapy option seems effective, even in recurrent cases, and valid, particularly for those at high risk of surgery or who do not prefer it.